Complaint Proceedings in Warranty and Guarantee - Muzyka, Magdalena; Śmiechowska, Maria (Studia Oeconomica Posnaniensia, 2018)
The purpose of this paper is to compare the legal status of consumer protection before and after 25th December 2014, when a significant change in regulations occurred in this area, as well as an indication of significant differences between the manufacturer’s warranty protection and law regulated bailment. The awareness of consumer rights is still growing. However, the distinction between the complaint submitted on the basis of the warranty to the manufacturer, and the complaint under the warranty addressed to the seller due of individual rights titles still brings many difficulties. The work presents a detailed analysis of the differences between the warranty, which results from the provisions of law and a guarantee which is a voluntary declaration by the manufacturer regarding the quality of his/her products. Currently, with the changing market model, in which one can observe the transition of enterprises from the orientation directed to the product, its characteristics, quality and price, to the one, which puts the customer’s needs at the center of interest. Therefore, aspects related to after-sales service are gaining importance. This is an overview paper.